2021
DOI: 10.1111/jocd.14086
|View full text |Cite
|
Sign up to set email alerts
|

The significance of endocan immunohistochemical expression in chronic plaque psoriasis

Abstract: Background Psoriasis is a chronic inflammatory skin disease with immune‐mediated mechanism. Endocan is a soluble dermatan sulfate proteoglycan expressed by endothelium of blood vessels. Aims The present study aims to evaluate immunohistochemical localization of endocan in psoriatic skin in comparison with normal skin and to correlate its expression with the clinical and pathological data of psoriasis. Patients/Methods Skin biopsies from 36 psoriatic patients and 40 normal subjects were taken and processed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Histopathological and immunohistochemistry analysis may be a useful tool for decoding physiopathological mechanisms in psoriasis, such as the recruitment of circulating lymphocytes to inflammatory sites and their Lymphocyte Function-Associated Antigen 1 (LFA-1) dependent adhesion stimulated by endocan [54]. The cytotoxicity of CD8+ T cells and Natural Killer (NK) cells has also been found to be mediated by the perforin/granzyme pathway, explaining why perforin expression is upregulated in activated CD8+ T cells, which are abundantly expressed in the epidermis of psoriasis plaques [55].…”
Section: Histopathologymentioning
confidence: 99%
“…Histopathological and immunohistochemistry analysis may be a useful tool for decoding physiopathological mechanisms in psoriasis, such as the recruitment of circulating lymphocytes to inflammatory sites and their Lymphocyte Function-Associated Antigen 1 (LFA-1) dependent adhesion stimulated by endocan [54]. The cytotoxicity of CD8+ T cells and Natural Killer (NK) cells has also been found to be mediated by the perforin/granzyme pathway, explaining why perforin expression is upregulated in activated CD8+ T cells, which are abundantly expressed in the epidermis of psoriasis plaques [55].…”
Section: Histopathologymentioning
confidence: 99%
“…Few studies examined available biomarkers of endothelial function in psoriasis patients, and the results obtained were in line with the findings of functional vascular studies. Abdou et al reported that psoriatic skin exhibited over-expression of endocan (a proteoglycan expressed by endothelial cells), reflecting the ongoing endothelial activation and neovascularization [ 211 ]. Similarly, Balta et al reported increased level of circulating endocan in psoriasis patients, which also correlated with PASI, hsCRP and cIMT [ 212 ].…”
Section: Deleterious Effects Of Increased Systemic Oxidative Stress A...mentioning
confidence: 99%